The code less traveled: The transition to teletherapy - Lauren A. Stutts (SSM - Mental Health, 2022)
Teletherapy became commonplace as a result of the pandemic, and it is an effective modality for psychological treatment. In this essay, the author narrates the transition from a group in-person practice to an individual teletherapy-only practice. Subsequently, she highlights benefits and practical uses of teletherapy. Lastly, she notes some of the limitations and solutions to them. Teletherapy should continue to be evaluated and adjusted, but it is a sustainable option for psychological treatment in the 21st century.